The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.7127/rbai.v13n2001054
|View full text |Cite
|
Sign up to set email alerts
|

Coordenadas Geográficas E Altitude Na Estimativa Da Temperatura Do Ar No Estado De Goiás

Abstract: RESUMOA estimativa de dados meteorológicos é imprescindível quando não se dispõe de dados observacionais. No entanto, a confiabilidade no uso destes, está condicionada a existência de concordância entre os dados preditos e os observados. Particularmente para a variável temperatura do ar, sendo uma das mais importantes para o planejamento das atividades agrícolas. Diante disso, objetivou-se com este trabalho, estimar os valores máximos, mínimos e médios da tempetura do ar, na escala decendial, a partir de coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
1
0
2
Order By: Relevance
“…Several authors have used these variables to estimate air temperature, for instance, Medeiros et al (2005), who estimated the average air temperature for the Northeast of Brazil using multiple linear regression equations and obtained an adjusted coefficient of determination (R2adj) of 0.87. Capuchinho et al (2019) estimated the maximum (Tmax), minimum (Tmin), and average (Tavg) air temperatures also using multiple linear regression techniques and observed adjusted coefficients of determination ranging from 0.66 to 0.82 for Tmax, 0.56 to 0.72 for Tmin, and 0.66 to 0.74 for Tavg, with high precision and accu-racy for the municipalities of Goiás. Another interesting paper, by Yu et al (2021), who used a geographically weighted regression model to estimate the surface air temperature lapse rate in mainland China, concluded that the model had a strong predictive ability for surface air temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have used these variables to estimate air temperature, for instance, Medeiros et al (2005), who estimated the average air temperature for the Northeast of Brazil using multiple linear regression equations and obtained an adjusted coefficient of determination (R2adj) of 0.87. Capuchinho et al (2019) estimated the maximum (Tmax), minimum (Tmin), and average (Tavg) air temperatures also using multiple linear regression techniques and observed adjusted coefficients of determination ranging from 0.66 to 0.82 for Tmax, 0.56 to 0.72 for Tmin, and 0.66 to 0.74 for Tavg, with high precision and accu-racy for the municipalities of Goiás. Another interesting paper, by Yu et al (2021), who used a geographically weighted regression model to estimate the surface air temperature lapse rate in mainland China, concluded that the model had a strong predictive ability for surface air temperature.…”
Section: Introductionmentioning
confidence: 99%
“…, a temperatura do ar é o fator climático que mais exerce influência de forma direta e significativa sobre os processos fisiológicos de seres vivos. De acordo comCapuchinho et al (2019), este fator climático também é responsável por influenciar diversas atividades econômicas desenvolvidas pela sociedade, em seus múltiplos aspectos. A variabilidade climática deve ser considerada em diversos setores, como economia, pecuária, engenharia e produção de energia (MEDEIROS; HOLANDA, 2019).Nesse contexto, o zoneamento climático das regiões, ou seja, a divisão da área em unidades individualizadas segundo as suas características, contribui para registrar e delimitar o potencial físico e biológico para a manutenção dos recursos naturais, existentes em cada Revista Equador (UFPI), Vol.…”
unclassified
“…ISSN: 2317 Home: http://www.ojs.ufpi.br/index.php/equador localidade. Essa demanda pelo zoneamento parte da necessidade de promover o conhecimento sobre cada território.De acordo comFilgueiras et al (2016), devido ao elevado espaçamento da rede de estações meteorológicas, a correlação entre os dados obtidos pelas estações meteorológicas com os dados estimados por sensoriamento remoto promove a possibilidade de determinar valores proporcionais aos dados de temperatura do ar em áreas onde a disponibilidade de dados meteorológicos é escassa ConformeCapuchinho et al (2019), diferentes métodos têm sido utilizados a fim de se obter maior exatidão nas estimativas de temperatura do ar onde os dados meteorológicos são ausentes, a fim de contornar as limitações decorrentes da falta destes registros climáticos.…”
unclassified